Attendance at early recall and colposcopy in routine cervical screening with human papillomavirus testing. Issue 8 (24th October 2020) - Green, Leonardo I.; Mathews, Christopher S.; Waller, Jo; Kitchener, Henry; Rebolj, Matejka; ,
Abstract: Attendance at early recall and colposcopy is crucial to attaining the benefits of primary high‐risk human papillomavirus (HR‐HPV)‐based screening. Within the English HPV pilot, we analysed deprivation‐ and age‐related patterns of attendance at colposcopy and 12‐ and 24‐month early recall of HR‐HPV positive women screened in 2013 to 2015 (N = 36 466). We fitted logistic regression models for adjusted odds ratios (OR). Despite high overall attendance, area deprivation had a small but significant impact at both early recalls, for example, attendance at 24 months was 86.3% and 83.0% in less vs more deprived areas, respectively (ORadj : 0.76; 95% CI: 0.67‐0.87). Older women (≥30 years) were more likely to attend early recall than younger women (<30 years), for example, attendance at 24 months was 86.1% vs 82.3%, respectively (ORadj : 1.32, 95% CI: 1.16‐1.51). Most women attended colposcopy following a baseline referral, with 96.9% attendance among more deprived and 97.8% among less deprived areas (ORadj : 0.70; 95% CI: 0.55‐0.88). Differences in colposcopy attendance by deprivation level at 12 and 24 months were of approximately the same magnitude. In conclusion, attendance at early recall and colposcopy was reassuringly high. Although there were statistically significant differences by deprivation and age group, these were small in absolute terms.